Jual Beli Kosmetik Bekas Dikalangan Mahasiswa - Yunita Ramlah Sari Siregar; Nursania Dasopang (Jurnal El-Thawalib, 2022)
Muamalah is God's rule that regulates human relations with humans in meeting needs either by exchanging goods or something useful. In muamalah, buying and selling is the most important activity, such as buying and selling used cosmetics. Used cosmetics are traded by students at the Padangsidimpuan State Islamic Institute. Used cosmetics come from personal property and some items that are deposited for resale. Used cosmetics are offered with several details such as price and product conditions.The main problem in this study is how the practice of buying and selling used cosmetics among students of the Padangsidimpuan State Islamic Institute and how the fiqh muamalah review of the practice of buying and selling used cosmetics.This research uses the field research method (field research). Data collection techniques used in this study were observation, interviews and documentation. Data analysis was carried out using the text method which was sourced from the research subject, namely the sources of sellers and buyers of used cosmetics.The results showed that the practice of buying and selling used cosmetics among students of the Padangsidimpuan State Islamic Institute did not provide clear information about the product, used cosmetics were sold without product packaging boxes, and the unbalanced content of cosmetics with the prices of used cosmetics. The review of muamalah fiqh in the practice of selling used cosmetics carried out by students violates the basic principles of muamalah, namely the object being traded is not clear because it is speculative or vague, it is forbidden to be traded because used cosmetic products sold do not yet have BPOM notification and Halal label. This buying and selling should be done on the basis of attracting benefits and rejecting harm. In practice, buyers do not feel the benefits of buying used cosmetics because the contents of the cosmetics have been widely used before and the cleanliness and safety of the products are not guaranteed so that buyers get negative effects from using products such as acne, irritation, and reddened skin. For sellers, this activity is caused by the desire to sell used cosmetics to get money back and there are also those who are no longer suitable for using these cosmetic products.